ДИГИТАЛЬНЫЙ ВЕКТОР СОВРЕМЕННОЙ МЕДИАКУЛЬТУРЫ - ЛАНДЯК, О. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Интенсивное внедрение цифровых технологий определяет специфику развития "новых медиа", их влияние на когнитивную сферу и, как следствие, новейшие процессы культурогенеза. Исследована специфика дигитального вектора в современной медиакультуре, рассмотрено понятие дигитального вектора в контексте современных теорий медиакультуры и дигитальной культуры, обозначены возможные сценарии культурогенеза в ситуации дигитального вектора развития современной медиакультуры. Ландяк О. М. ДІГІТАЛЬНИЙ ВЕКТОР СУЧАСНОЇ МЕДІАКУЛЬТУРИ Інтенсивне впровадження цифрових технологій визначає специфіку розвитку "нових медіа", їх вплив на когнітивну сферу і, як наслідок, новітні процеси культурогенезу. Досліджено специфіку дигитального вектора в сучасній медіакультурі, розглянуто поняття дигитального вектора в контексті сучасних теорій медіакультури та дигитальної культури, позначені можливі сценарії культурогенезу в ситуації дигитального вектора розвитку сучасної медіакультури. Ключові слова: "нові медіа", дигітальний вектор, культурогенез, медіакультура Landyak O.M. DIGITAL VEKTOR OF THE MODERN MEDIACULTURE Along with the "iconic turn" modern media culture is characterized by its digital focus. The intensive use of digital technology determines the specificity of "new media" and their influence on cognition and, consequently, new processes of cultural genesis. The digital vector of modern media culture generates ambivalence of the genesis of culture scripts. On the one hand, the further development of modern media culture understood to be the "loss of will" replace reality substitutes digital culture in the critique of the capitalist consumer society. However, it becomes more and more important concept of "technocratic optimism," examines the digital vector of modern media culture in its creative aspect, namely as a catalyst of many self-valuable cultural codes that can transmit cultural genome and promote further creativity of the media culture. The specific of the digital vector in the modern media culture was investigated, the concept of digital vector in the context of contemporary theories of media culture and digital culture was considered, the possible scripts of cultural processes in the situation of digital vector of modern media culture were identified. In the context of current theoretical discourses a statement of special vector of development of media culture, which can be roughly described as digital vector was distinguished. The characteristic of the new concept in modern media culture digital practices, based on the one hand, on the increasingly popular online culture and the spaceless communicative possibilities of digital technologies, on the other - cognitive mythologems of the mental and physical freedom, generated by digital culture were considered. Key words: "new media", digital vector, cultural genesis, media culture